Nanogel Formulation of Butterfly Pea Flower Extract (Clitoria ternatea L.) Against Propionibacterium acnes Bacteria Inhibitory Test - Niluh Puspita Dewi; Radhika; Magfirah; Indah Kurnia Utami; Yasinta Rakanita; Nur Ramadhani; Nuraisya; Ni Ketut Marlina (Jurnal Penelitian Pendidikan IPA, 2026)
The chemical components of butterfly pea flowers (Clitoria ternatea L.) have a strong bacterial inhibition zone. The aim of this research is to make nanogels using the active ingredient ethanol extract of butterfly pea flowers and demonstrate the antibacterial activity of nanogels against Propionibacterium acnes bacteria. Because nanogels are more stable, translucent, and have small particle sizes making them efficient in releasing active chemicals and increasing bioavailability, nanogels are used in tropical medicine. Maceration is the extraction technique used. Nanogel of butterfly pea flower ethanol extract (BPFEE) was added to the nanogel formulation at concentrations of F1 (5%), F2 (10%), and F3 (15%). Transmission testing is part of the ideal formula; Other tests for characterization include phytochemical, organoleptic, particle size, pH, adhesion, spreadability and viscosity tests. Next, antibacterial activity was tested against Propionibacterium acnes using the well method. The research results showed that the % transmittance was 84-88%, the organoleptic results were in the form of a gel, color and distinctive aroma, particle size 114.9 – 283.9 mm, pH 5.6 – 6, adhesive power 1.36 – 2.1 seconds, spreadability 4.8-5.6 cm, viscosity 4071 – 3043.75 mPa.S. Telang flower ethanol extract nanogel can inhibit the growth of P. acnes bacteria, namely 8.2-11.7 mm.